Pentingnya Etika Public Relations Melalui Media Sosial Mengenai Kasus Pelecehan Seksual Di KRL Commuter Line - Khisma Rahmitha Rivka Yani; Putri Nabila (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Social media is currently experiencing extraordinary growth and development. Public relations ethics is one form of communication that must be applied in social media. Communiter Line is the Twitter account of PT KAI Commuter in Indonesia. But unfortunately, the account is considered to violate public relations ethics in social media. This research is entitled